Effect of a multicomponent nutritional supplement on functional outcomes for Duchenne muscular dystrophy: A randomized controlled trial. Issue 7 (July 2021) - Davidson, Zoe E.; Hughes, Ian; Ryan, Monique M.; Kornberg, Andrew J.; Cairns, Anita G.; Jones, Kristi; Hutchence, Meghan; Sampaio, Hugo; Morrison, Margot; Truby, Helen
Summary: Background & aims: Duchenne muscular dystrophy (DMD) is an X-linked neuromuscular condition causing progressive muscle weakness and premature death. Whilst effective treatments such as gene therapy are developed, families often seek complementary therapies such as nutrition supplements to help their son maintain function; however, there is limited evidence supporting the use of nutritional supplements in DMD. This study aimed to compare the effect of a Standard nutritional supplement with an Enhanced nutritional supplement combining three nutriceuticals on functional outcomes in ambulatory boys with Duchenne muscular dystrophy (DMD). Design: A 50-week double blinded, randomized, controlled crossover trial was conducted in four Australian neuromuscular centres. Primary outcome measures were 6-min walk distance (6MWD) and community ambulation (StepWatch™ Activity Monitoring). Secondary outcome measures included body composition and quality of life. Serum 25-hydroxyvitamin D was measured. Results: Twenty-seven boys completed the intervention. Traditional crossover analysis demonstrated the Enhanced supplement compared to the Standard supplement was associated with a difference of +12 (95% CI: −16, 40) metres in 6MWD, +0.5 (95% CI: −53, 54) inactive minutes per day and −95 (95% CI: −887, 696) steps per day. A mixed effect model indicated a potentially clinically important effect of the Enhanced supplement on the 6MWD of +31 (95% CI: −19, 81) metres. Mean serum 25 hydroxyvitamin D levels at week 50 was 94 (95% CI: 84, 104) nmol/L. There was no observable effect of either supplement regime on body composition or quality of life. Conclusions: Whilst a positive effect of the Enhanced supplement on functional outcomes was observed, this finding was inconclusive due to the small sample size. The results do not support the use of combined nutritional supplements to improve body composition or quality of life in DMD. A dose of 2000 IU vitamin D was an adequate dose to raise serum 25-hydroxyvitamin D over 50 weeks. Clinical trial registry: Registry #: ACTRN12610000462088, http://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?ACTRN=12610000462088 .